2018
DOI: 10.1016/j.cr.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Illumination of neural development by in vivo clonal analysis

Abstract: Single embryonic and adult neural stem cells (NSCs) are characterized by their self-renewal and differentiation potential. Lineage tracing via clonal analysis allows for specific labeling of a single NSC and tracking of its progeny throughout development. Over the past five decades, a plethora of clonal analysis methods have been developed in tandem with integration of chemical, genetic, imaging and sequencing techniques. Applications of these approaches have gained diverse insights into the heterogeneous beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…To investigate whether neuronal diversity originates from individual RGCs, we set out to develop a single-cell lineage-tracing system in the mouse hypothalamus. Our previous reports demonstrated that MADM (mosaic analysis with double markers) reporter mice in combination with CreER T2 driver mice are a genetic tool for spatially and temporally specific clonal analysis of dividing neural progenitors (Wong et al, 2018;Xu et al, 2018).…”
Section: Fate Multifurcation Of Single Rgcs Revealed By In Vivo Clona...mentioning
confidence: 99%
“…To investigate whether neuronal diversity originates from individual RGCs, we set out to develop a single-cell lineage-tracing system in the mouse hypothalamus. Our previous reports demonstrated that MADM (mosaic analysis with double markers) reporter mice in combination with CreER T2 driver mice are a genetic tool for spatially and temporally specific clonal analysis of dividing neural progenitors (Wong et al, 2018;Xu et al, 2018).…”
Section: Fate Multifurcation Of Single Rgcs Revealed By In Vivo Clona...mentioning
confidence: 99%
“…1A). Albeit many results from transplantation experiments, retroviral lineage tracing, genetic fate mapping, and in vivo clonal analysis point toward the hypothesis of multipotent progenitors with strict temporal coding [17][18][19][20][21], it is still possible that a majority of multipotent NPCs coexist with a minority of fate-specified progenitors that remain to be identified. More importantly, both hypotheses support the predetermined model in which the fate of cortical progenitors is pre-specified to produce projection neurons by either a temporal code or an inherent genetic program.…”
Section: Predetermined Strategymentioning
confidence: 99%
“…It is also unclear how deterministic and stochastic factors shape the cascade diversifying trajectory during lineage progression. Single-cell lineage tracing by integrating an inducible barcoding approach with transcriptomic data may be able to systematically record the developmental trajectory of each individual NPC [ 21 ].…”
Section: Cascade Diversifying Strategymentioning
confidence: 99%